Hâce Emir’in Efsâne-i Türkî adlı eseri (Vr. 1-50) inceleme – metin – dizin - Alam, Md Meraj (My University, 2019)
İlhanlı ve Altınordu dönemlerinde ortaya çıkan Doğu Türkçesi, Timurlular döneminde özellikle de XV. yüzyılda gelişen ve XX. yüzyıla kadar yaklaşık beş asır boyunca resmî ve edebî dil olarak kullanılan tarihî bir Türk lehçesidir.

Eastern Turkish, which emerged during the Ilhanli and Altinordu periods, developed during the reign of Timurids in the 15th century and was used as an official and literary language between 15th-19th centuries.
Keywords: Aşk hikāyesi Legend; Central Asia; Doğu Türkçesi; Eastern Turkish; Efsane; Hint Altkıta; History and criticism; Hüdabahş Doğu Kütüphanesi; Khuda Bakhsh Oriental Library; Love story; Orta Asya; Tarih ve eleştiri; the Indian subcontinent; Turkish literature; Türk edebiyatı